Influence of glass fibre post length and remaining dentine thickness on the fracture resistance of root filled teeth - Junqueira, R. B. [UNESP]; de Carvalho, R. F. [UNESP]; Marinho, C. C. [UNESP]; Valera, M. C. [UNESP]; Carvalho, C. A.T. [UNESP] (Wiley, 2017)
Aim: To evaluate, ex vivo, the influence of glass fibre post length and remaining thickness of dentine on the fracture resistance of bovine roots, after thermomechanical ageing. Methodology: Ninety bovine roots of the same size were root filled and randomly distributed into nine groups (n = 10), according to the root weakening protocol (NW – nonweakened; MW – medium weakened; HW – highly weakened) and post length (7 mm; 9 mm and 12 mm). The weakening of roots was performed using diamond burs, resulting in different thicknesses of remaining dentine. The post spaces were prepared, and in the weakened roots, the glass fibre posts were customized with composite resin, to create posts matching the canal size. Chemically activated resin cement was used to lute the posts. After luting, full crowns made of composite resin were attached to a silicon matrix. To reproduce physiological mobility, the roots were covered with polyether and embedded in polyurethane. The thermomechanical cycling was performed (1 200 000 cycles; 88N; 3,8 Hz; 5 ± 1 °C to 55 ± 1 °C). Then, the specimens were subjected to compressive force in a universal testing machine (1 mm min−1; 100 kgf) to analyse the fracture resistance. The specimens were analysed through a stereomicroscope to classify the failure mode (repairable/catastrophic). The values were subjected to statistical analysis (two-way anova and Tukey's test at 5%). The frequencies of failure mode were compared using chi-square test. Results: The association between length and dentine thickness was significant (P > 0.05). The difference was between NW and HW roots for posts of 12 mm in length. There was an association between failure mode and the length and remaining dentine thickness. Conclusions: Reduced dentine thickness in roots with longer posts had lower fracture resistance values, as catastrophic failure was more predominant.
Keywords: dentine thickness; fracture resistance; glass fibre posts; post length; weakening